Expert system diagnoses skin diseases using web-based Forward Chaining method - Taena, Ignasia Wanty; kelen, Yoseph pius kurniawan; Ludji, Dian Grace (Universitas Trunojoyo Madura, 2025)
The skin is an essential part of the human body that plays a role in protection, temperature regulation, and sensation. Maintaining skin health is crucial because skin infections can arise from bacteria, viruses, fungi, and parasites, and often spread through direct contact. Environmental factors, such as the availability of clean water, are among the main causes of skin diseases. Unfortunately, many people consider skin diseases to be trivial, whereas if left untreated, these conditions can become fatal. A lack of understanding and information often leads to delayed treatment.To address this issue, an expert system has been developed to enable early diagnosis of skin diseases. This system uses the forward chaining method, an approach that starts from initial facts and moves toward a conclusion through a structured series of questions. One of the advantages of this method is its ability to process limited data into useful and accurate information. The expert system is designed as a web-based application to ensure broader public access.The diseases that can be diagnosed include ringworm, tinea versicolor, scabies, chickenpox, boils, dermatitis, rhinitis, and urticaria. This system is expected to help the public in recognizing symptoms of skin diseases and provide early support before consulting a doctor. Based on previous research, the lack of disease and symptom data was a challenge. Therefore, this study added 15 types of skin diseases and 20 symptom data points.For future development or further research, it is recommended to expand the system with more types of diseases, different diagnostic methods, and additional features to improve accuracy and user-friendliness in diagnosing skin diseases. Test data from 30 users showed a 90% accuracy rate, indicating that the expert system successfully helps users and provides solutions.Keywords: Expert System, Forward Chaining, Skin Disease, Early Diagnosis dini, Web